Primate Adaptation and Evolution - Fleagle, John G (San : Diego Academic press, 1999)
John Fleagle has improved on his 1988 text by reconceptualizing chapters and by bringing new findings in functional and evolutionary approaches to bear on his synthesis of comparative primate data. The Second Edition provides a foundation upon which students can develop an understanding of our primate heritage. It features up-to-date information gained through academic training, laboratory experience and field research. This beautifully illustrated volume provides a comprehensive introductory text explaining the many aspects of primate biology and human evolution. Provides up-to-date information about many aspects of primate biology and evolution Contains a completely new chapter on primate communities Presents totally revised chapters on primate origins, early anthropoids, and fossil platyrrhines Includes an updated glossary, new illustrations, and a revised Classification of Order Primates Succeeds as the best introductory text on primate evolution because it synthesizes and allows access to primary literature
Included bibliographical references.; Glossary 571-576p.; Index 581-596p.
Keywords: Adaptative; Evolution; Evoluttie adaptie; Anthropology